Human-Hair Bifurcated Tumplines from Old Man Cave, Utah. Issue 4 (2nd October 2021) - Geib, Phil R.; Webster, Laurie D.; Ahrens, Kami
Abstract : Unwrapping a bundle of Basketmaker II textiles from Old Man Cave disclosed two examples of a previously undocumented textile form: bifurcated tumplines. At more than twice the width of standard tumplines, these warp-faced plain weave bands of human hair cordage have one flat end, with the other splitting into two separate parallel bands—one longer and the other shorter. Both narrow bands terminate in tumpline suspension loops. Strains, breaks, and repairs indicate that these textiles served to carry loads. Rather than suspending the weight from the head and resting it on the back, this tumpline suspended weight in front with the textile draped over the shoulder. Knowledge of this new tumpband form allowed identification of an additional example in a museum. Radiocarbon dating confirms the Basketmaker II temporal affiliation. Final use of the Old Man Cave bifurcated tumplines was as a pair and likely related to transporting bodies for burial.